(untitled) (Bioscience Journal, 2017)
The jau, Zungaro jahu (Ihering, 1898) is an endangered species, rheophilic, reaching 1.5 m and more than 100 kg. During a work of microbiological monitoring of water quality, in the cultivation of Zungaro jahu, microorganisms that were isolated, were previously reported in other studies, as family members Enterobacteriaceae, Staphylococcus and non-fermenting bacilli. However, it was also isolated Chromobacterium violaceum, which despite being a bacterium found in such an environment, it was reported linked to the cultivation of fish. This paper describes the Chromobacterium violaceum founded in a psiculture, which has implications for national fish farming.